The Effect of Enriched Environment on the Outcome of Traumatic Brain Injury; A Behavioral, Proteomics, and Histological Study - Kovesdi, Erzsebet; Gyorgy, Andrea B.; Kwon, Sook-Kyung C.; Wingo, Daniel L.; Kamnaksh, Alaa; Long, Joseph B.; Kasper, Christine E.; Agoston, Denes V. (Frontiers in Neuroscience, 2011)
De novo hippocampal neurogenesis contributes to functional recovery following traumatic brain injury (TBI). Enriched environment (EEN) can improve the outcome of TBI by positively affecting neurogenesis. Blast induced traumatic brain injury (bTBI) characterized by memory impairment and increased anxiety levels, is a leading cause of chronic disability among soldiers. Using a rodent model of bTBI we asked: a) whether long-term exposure to EEN after injury can ameliorate behavioral abnormalities and b) what the effects of EEN are at the molecular and cellular levels and on de novo neurogenesis. We found that housing injured animals in EEN resulted in significantly improved spatial memory while animals in normal housing (NH) showed persistent memory impairment. VEGF and Tau-protein but not IL-6 levels were normalized in the dorsal hippocampus (DHC) of EEN rats while all three markers remained elevated in NH rats. Interestingly, after peaking at 6 weeks post-injury, anxiety returned to normal levels at 2 months independent of housing conditions. Housing animals in EEN had no significant effect on VEGF and Tau-protein levels in the ventral hippocampus (VHC) and the amygdala (AD). We also found that EEN reduced IL-6 and INF levels in the VHC; these markers remained elevated following NH. We observed an increase in GFAP and DCX immunoreactivities in the VHC of NH animals at 2 months post-injury. Conversely, injured animals housed in EEN showed no increase in GFAP or DCX immunoreactivity in their VHC. In summary, long-term exposure of injured animals to EEN appears to play a positive role in the restoration of memory functions but not on anxiety, which returned to normal levels after a significant period of time. Cellular and molecular changes in response to EEN appear to be a part of neurogenesis-independent as well as dependent recovery processes triggered by bTBI.